Pelaksanaan Corporate Social Responsibility Dan Zakat Perusahaan Perbankan Syari’ah Di Madura - Hariyanto, Erie; Humaidy, Mohammad Ali Al (UI Scholars Hub, 2019)
Corporate Social Responsibility and corporate zakat programs are two instruments for distributing with social responsibility funds that both have a legal basis, namely Law No.40 of 2007 concerning with Limited Liability Companies and company zakat, Law No.23 of 2011 concerning Zakat Management. In general, zakat and CSR contain the same vision and mission, namely concern for the overall social condition. Particularly, the life of the community is related to the welfare, security and peace of the people. The present study uses qualitative methods. The results of the research are Firstly, Bank BPRS Bhakti Sumekar Sumenep has form of Sharia Business Financing program activities (PUSYAR iB), Commercial Banks of BRI Syariah Bank fulfill CSR and corporate zakat through the National Zakat Agency (Baznas). Secondly, The social responsibility activities of Islamic Financial Institutions (LKS) which base their business activities on Islamic sharia principles are to set aside a portion (2.5%) of the company's profits in the form of zakat payments. In general, the expenditure of zakat funds here is not merely to fulfill the administrative requirements of the country but also to obtain the blessing value as a company based on sharia principles.